Tennessee - Thompson, Kathleen (Milwaukee, WI : Raintree Publishers, 1986)
Discusses the history, economy, culture, and future of Tennessee. Also includes a state chronology, pertinent statistics, and maps.
"A Turner book."
3.9
5-8
Keywords: Tennessee -- Juvenile literature; Tennessee; Tennessee